Netscape breaks free. (Economist, 1998)
On March 31, 1998, Netscape, the company whose omnipresent browser made the Internet accessible to millions, will reveal the “source code” of the latest version of its software program. The move is a brave, or perhaps desperate, gamble in the firm's struggle to hold off Microsoft's attack on its market. Although many companies release their products, firms seldom reveal their source code, the actual lines of programming language that make the program function. Users will be permitted to change the software and even to reissue the new product under their own brand name. The only hitch is that the altered source code must then also be made accessible to anyone who requires it. The goal of this unconventional approach is to transform the whole Internet into a vast research division for Netscape's browser software.